2012
DOI: 10.1128/jb.00981-12
|View full text |Cite
|
Sign up to set email alerts
|

The Lysozyme-Induced Peptidoglycan N -Acetylglucosamine Deacetylase PgdA (EF1843) Is Required for Enterococcus faecalis Virulence

Abstract: f Lysozyme is a key component of the innate immune response in humans that provides a first line of defense against microbes. The bactericidal effect of lysozyme relies both on the cell wall lytic activity of this enzyme and on a cationic antimicrobial peptide activity that leads to membrane permeabilization. Among Gram-positive bacteria, the opportunistic pathogen Enterococcus faecalis has been shown to be extremely resistant to lysozyme. This unusual resistance is explained partly by peptidoglycan Oacetylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 46 publications
1
67
0
2
Order By: Relevance
“…When the eep gene was complemented back into the eep deletion mutant using a low-copy-number plasmid, the complement strain behaved similarly to the wild type, suggesting that the phenotype we observed was Eep dependent. Consistent with previous observations, the pgdA deletion mutant did not show any change in lysozyme susceptibility compared to that of the wild type (20), even though it is known to be regulated by SigV at the transcriptional level (4, 5). FA2-2 and mutants lacking eep and sigV in this genetic background were used as controls in this study to eliminate any strain bias in the lysozyme resistance mechanism.…”
Section: Deletion Of Eep Renders E Faecalis More Susceptible To Lysosupporting
confidence: 79%
See 1 more Smart Citation
“…When the eep gene was complemented back into the eep deletion mutant using a low-copy-number plasmid, the complement strain behaved similarly to the wild type, suggesting that the phenotype we observed was Eep dependent. Consistent with previous observations, the pgdA deletion mutant did not show any change in lysozyme susceptibility compared to that of the wild type (20), even though it is known to be regulated by SigV at the transcriptional level (4, 5). FA2-2 and mutants lacking eep and sigV in this genetic background were used as controls in this study to eliminate any strain bias in the lysozyme resistance mechanism.…”
Section: Deletion Of Eep Renders E Faecalis More Susceptible To Lysosupporting
confidence: 79%
“…Our present studies also confirmed the absence of a link between PgdA and lysozyme resistance in E. faecalis V583. PgdA does, however, contribute to lysozyme susceptibility in Streptococcus pneumoniae and virulence in animal models of infection (31)(32)(33), and recent evidence suggests that PgdA is linked to virulence in E. faecalis, as a mutant in pgdA was attenuated in a Galleria mellonella infection model (20). What role PgdA might be playing in a mammalian host during infection remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…difficile contains 10 putative polysaccharide deacetylases, of which only 1, encoded by pdaV, is significantly induced by V in a lysozyme-dependent manner. PdaV belongs to the PgdA family of polysaccharide deacetylases, several of which have been implicated in increased lysozyme resistance (19,20,24). We found that expression of pdaV in the csfV mutant increased lysozyme resistance and peptidoglycan deacetylation.…”
Section: Discussionmentioning
confidence: 73%
“…In B. subtilis, V is required for expression of oatA, which encodes a peptidoglycan O-acetyltransferase that increases lysozyme resistance (22,32,33). In E. faecalis, V is required for expression of a peptidoglycan deacetylase, PgdA (19,21). We found that in response to lysozyme, C. difficile V induces expression of a peptidoglycan deacetylase, which results in deacetylation of the C. difficile peptidoglycan.…”
Section: Figmentioning
confidence: 86%
See 1 more Smart Citation